Insula and sensory insular cortex and somatosensory control in patients with insular stroke. (30th March 2014) - Baier, B.; zu Eulenburg, P.; Geber, C.; Rohde, F.; Rolke, R.; Maihöfner, C.; Birklein, F.; Dieterich, M.
Abstract Background In functional imaging studies, the insular cortex (IC) has been identified as an essential part of the processing of a whole spectrum of multimodal sensory input. However, there are no lesion studies including a sufficient number of patients, which would reinforce the functional imaging data obtained from healthy subjects. Such lesion studies should examine how damage to the IC affects sensory perception. We chose acute stroke patients with lesions affecting the IC in order to fill this gap. Methods A comprehensive sensory profiling by applying a quantitative sensory testing protocol was performed and a voxel‐lesion behaviour mapping analysis in 24 patients with acute unilateral cortical damage was applied. Results Our data demonstrate that patients with lesions of the posterior IC have deficits in temperature perception, but did not show other sensory deficits such as hot or cold pain perception associated with specific lesion locations. Conclusion Our data allow the conclusion that the posterior IC may represent the major region responsible for encoding warm and cold perception in the brain. To what extent focal IC lesions may also impair pain processing or induce post‐stroke pain has to be addressed in future studies including more patients.